The Importance of Utilizing Media Relations to Improve the Image of an Agency - Azmi, Novia Amirah; Fitra, Reza Jannah Al (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Public relations plays an important role in building a positive image of the company. A positive image will give a good impression to the company which ultimately will also have an impact on increasing the number of customers. One effort to build a positive company image is to increase Brand Awareness through social media. The research method used is literature review. The results of the research are that the use of social media to improve or build a positive image is now widely used. Even celebrities use official social media accounts to brand themselves and their companies. The use of social media as a communication medium between universities and the public in an effort to improve the image of the university is one of the steps that can be taken by universities to socialize performance and other matters related to information about the university. Social media currently has multifunctions, not only used to communicate with each other but also used for other activities, one of which is promotional activities as an interaction effort between universities and the In using social media as the spearhead for conveying information, good planning is needed so that in its implementation social media can become a way to achieve the expected goals